2021
DOI: 10.3389/fmolb.2021.626600
|View full text |Cite
|
Sign up to set email alerts
|

Structural Profiling of Bacterial Effectors Reveals Enrichment of Host-Interacting Domains and Motifs

Abstract: Effector proteins are bacterial virulence factors secreted directly into host cells and, through extensive interactions with host proteins, rewire host signaling pathways to the advantage of the pathogen. Despite the crucial role of globular domains as mediators of protein-protein interactions (PPIs), previous structural studies of bacterial effectors are primarily focused on individual domains, rather than domain-mediated PPIs, which limits their ability to uncover systems-level molecular recognition principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This modulation of gene expression relies on the secretion of specific pathogenicity factors called effector proteins. Effectors' arsenal and their delivery system vary from species to species although they have the common aim to interfere with the host metabolism to their advantage, and to hamper the immune system, enhancing the pathogen survival and the development of the disease (10)(11)(12)(13). Advancing our knowledge about the functioning and success of biotic interactions is of prime importance towards improving plant health globally in an environmentally friendly context.…”
Section: Introductionmentioning
confidence: 99%
“…This modulation of gene expression relies on the secretion of specific pathogenicity factors called effector proteins. Effectors' arsenal and their delivery system vary from species to species although they have the common aim to interfere with the host metabolism to their advantage, and to hamper the immune system, enhancing the pathogen survival and the development of the disease (10)(11)(12)(13). Advancing our knowledge about the functioning and success of biotic interactions is of prime importance towards improving plant health globally in an environmentally friendly context.…”
Section: Introductionmentioning
confidence: 99%
“…Hijacking of host networks by the pathogen essentially works by imitation and competition with endogenous host–host interactions (Franzosa and Xia 2011 ; Yapici-Eser et al 2021 ). It has been observed that a majority of the pathogen proteins bind to the same domain on their respective host target that are otherwise bound by host endogenous proteins (Chen and Xia 2021 ). In addition to employing mimicking host domains, effectors also employ short linear motifs that bind to host domains with similar specificities as host endogenous proteins, albeit sharing little homology with the latter(Samano-Sanchez and Gibson 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such information has paved the way for system-level analyses of whole interactomes, leading to a better understanding of pathogenicity, disease progression, and human-pathogen coevolution ( 16 ). Further, the development of chemical crosslinking mass spectrometry (XL-MS) ( 17 , 18 ) and hydrogen-deuterium exchange mass spectrometry (HDX-MS) ( 19 , 20 ) has increased the resolution of these interactions by catalyzing the identification of protein-binding interfaces, which is of relevance for the uncovering of systems-level molecular recognition principles governing host-bacteria interactions ( 21 ). In addition, the accumulation of host-pathogen protein-protein interaction interfaces provides new opportunities to investigate the relationship between antibody responses and protein binding interfaces.…”
mentioning
confidence: 99%